Landscape Design: Finding Inspiration for a Design Theme - Gail Hansen; Erin Alvarez (EDIS)
ENH1169, a 4-page illustrated fact sheet by Gail Hansen and Erin Alvarez, suggests types of design themes, sources of inspiration, and how to incorporate a theme into a landscape design. Includes references. Published by the UF Department of Environmental Horticulture, July 2010.